Determing the number of regimes in a threshold autoregressive model using smooth transition autoregressions - Birgit Strikholm; Timo Teräsvirta (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
In this paper we propose a method for determining the number of regimes in threshold autoregressive models using smooth transition autoregression as a tool. As the smooth transition model is just an approximation to the threshold autoregressive one, no asymptotic properties are claimed for the proposed method. Tests available for testing the adequacy of a smooth transition autoregressive model are applied sequentially to determine the number of regimes. A simulation study is performed in order to find out the finite-sample properties of the procedure and to compare it with two other procedures available in the literature. We find that our method works reasonably well for both single and multiple threshold models.
Keywords: C22; C51; 330; Model specification; model selection criterion; nonlinear modelling; sequential testing; switching regression; Modell-Spezifikation; Zeitreihenanalyse; Theorie; Nichtlineares Verfahren; Autokorrelation